Design and Realization of Low profile Compact Wideband Monopole Printed Antenna for C and X band Application. Issue 1 (February 2021) - Ghosh, S; Sarkar, I; Chowdhury, S; Dutta, S; Dey, P; Majumdar, S; Ghosh, A; Sarkar, P P; Sarkar, D C
Abstract: A compact low profile printed line-fed antenna presented for wideband in C and X band range. The antenna proposed in this paper has wider impedance bandwidth at well separated resonance frequencies. The antenna has a circular slot in the radiating patch embedding a parasitic circular patch. A grounded metallic strip extended from the ground plane connected to the middle of the parasitic patch through a shorting pin for improved impedance bandwidth. Rectangular patch has a compact area of 32 mm X 30 mm. thickness of the annular-slot in the patch and width of grounded strip have been varied to provide the surface waves within the microstrip antenna responsible for large frequency ratio. The simulated result shows that fractional impedance bandwidth of about 660 MHz, 1.54GHz, 440MHz centred at 2.87GHz, 6.17GHz and 8.15GHz respectively. To maintain the impedance bandwidth within C and X band operation, parametric study has been reported. The antenna shows absolute gain 1.12 dBi at 3.19 GHz. The proposed wideband slot antenna has been studied and designed for simulation results of return losses; radiation patterns, realized peak gains, and efficiencies of the antenna are presented. The projected antenna is appropriate for the applications in C and X bands such as medical and industrial heating applications (5.725 - 5.875 GHz), mobile satellite sub-band (7.975-8.025 GHz), Radiolocation for Military requirement for land, airborne and naval radars (8.5 GHz- 10.5 GHz).